Optimalisasi Penerimaan Negara dari Cukai Minuman Mengandung Etil Alkohol: Analisis Data Mikro - Mohtar Rasyid (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
This study aims to evaluate the potential government revenue from alcoholic baverages (MMEA) excise. To measure the potential revenue from MMEA, this study uses a micro consumption database of household consumption for MMEA published by the Central Statistics Agency (BPS) in the SUSENAS. Data on consumption of MMEA is converted in standard units (liters) and multiplied by the new excise tax rate. The estimation results of excise receipts from MMEA indicate that the magnitude of the potential for excise duty can reach around IDR 9 Trillion. While the actual state revenue from MMEA excise is still in the range of IDR 5 to 6 Trillion. This finding indicates that Indonesia’s current MMEA excise tax revenue is relatively unoptimal. Some major suggestions conveyed in this study are:(a) the need to increase enforcement efforts so that excise violations can be minimized;, and (b) the need to introduce traditional MMEA into the MMEA excise scheme so that the excise control function for alcoholic drinks can be further improved.